2022
DOI: 10.1002/cti2.1374
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory marker trajectories associated with frailty and ageing in a 20‐year longitudinal study

Abstract: Objective The aim of this exploratory study was to investigate the development of low‐grade inflammation during ageing and its relationship with frailty. Methods The trajectories of 18 inflammatory markers measured in blood samples, collected at 5‐year intervals over a period of 20 years from 144 individuals aged 65–75 years at the study endpoint, were related to the degree of frailty later in life. Results IFN‐γ‐related markers and platelet activation markers were found to change in synchrony. Chronically ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 70 publications
2
10
1
Order By: Relevance
“…Also, the two commonly used definitions of frailty are very different and should rather be used as complementary frailty tools than substitutions for each other [ 49 ]. Our findings of an association between inflammation and frailty measured as FI as well as an association between frailty and monocyte-specific gene expression is supported by previous findings of an association between CRP and IL-6 with frailty using both Fried’s [ 25 , 26 , 38 , 39 ] and FI definition [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Also, the two commonly used definitions of frailty are very different and should rather be used as complementary frailty tools than substitutions for each other [ 49 ]. Our findings of an association between inflammation and frailty measured as FI as well as an association between frailty and monocyte-specific gene expression is supported by previous findings of an association between CRP and IL-6 with frailty using both Fried’s [ 25 , 26 , 38 , 39 ] and FI definition [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…Higher levels of cathepsin S have shown to be associated with pro-inflammatory markers [ 36 ], as well as higher levels of CRP and IL-6 [ 37 ]. Furthermore, longitudinal studies have shown that chronic inflammation is associated with frailty, especially in women [ 9 , 38 ]. In midlife, stable low levels of CRP were linked to lower odds of frailty in later life [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data revealed that elevated levels of IL-6 pathway markers, namely CRP and sIL-6R, were associated with more frailty and reduced physical strength. Other associations were detected in women, notably increasing sCD14 levels and frailty, an indicator of monocyte overactivation ( 287 ). In contrast, in a recent longitudinal study of a large birth cohort ( n = 1,091) the physical frailty phenotype and frailty index were both used to assess frailty in participants 12 yr apart.…”
Section: The Physiological Phenotype Of Frailtymentioning
confidence: 99%
“…Moreover, K1 treatment was shown to reduce the expression of interleukin-6 (IL-6) mRNA in THP-1 cells (human macrophages) treated with LPS [ 33 ]. IL-6 has been implicated in the pathology of a wide range of diseases, including coronary artery disease (CAD) [ 37 ], which contributes to diabetes [ 38 ], aging [ 39 , 40 ] and cancer progression [ 41 ]. IL-6 activates major signaling pathways: the Janus-activated kinase-signal transducer and activator of transcription (JAK)-STAT) pathways, the Ras/Raf mitogen-activated protein kinase (MAPK, MEK/ERK) signaling cascade, and the phosphatidylinositol 3-kinase-dependent (PI3K/AKT) pathway [ 42 , 43 , 44 ].…”
Section: Vitamin K In Cell Biologymentioning
confidence: 99%